Choosing a Nursing Home: What Do Consumers Want to Know, and Do Preferences Vary across Race/Ethnicity?. (11th February 2016) - Hefele, Jennifer Gaudet; Acevedo, Andrea; Nsiah‐Jefferson, Laurie; Bishop, Christine; Abbas, Yasmin; Damien, Ecaterina; Ramos, Candi
Abstract : Objective: To identify what consumers want to know about nursing homes (NHs) before choosing one and to determine whether information preferences vary across race/ethnicity. Data Sources/Study Setting: Primary data were collected in Greater Boston (January 2013–February 2014) from community‐dwelling, white, black, and Latino adults aged 65+ and 40–64 years, who had personal/familial experience with a NH admission or concerns about one. Study Design: Eleven focus groups and 30 interviews were conducted separately by race/ethnicity and age group. Principal Findings: Participants wanted detailed information on the facility, policies, staff, and residents, such as location, staff treatment of residents, and resident conditions. They wanted a sense of the NH gestalt and were interested in feedback/reviews from residents/families. Black and Latino participants were especially interested in resident and staff racial/ethnic concordance and facility cultural sensitivity. Latino participants wanted information on staff and resident language concordance. Conclusions: Consumers want more information about NHs than what is currently available from resources like Nursing Home Compare. Report card makers can use these results to enhance their websites, and they should consider the distinct needs of different racial/ethnic groups. Future research should test methods for collecting and reporting resident and family feedback/reviews.